Filogenia molecular e filogeografia do gênero Salminus (Characiformes) - Silva, Carolina de Barros Machado da (2016)
Salminus is a genus comprised of four Neotropical medium- and large-sized fishes species, top predators, with both recreational and commercial importance. The paucity of information on taxonomy, phylogeny and phylogeography make appropriate conservation policies difficult for the genus, which is in a significant population decline. For this reason, our goal was, by using mitochondrial (COI, Cytb and D-loop) and nuclear (RAG2 and S7 intron) molecular makers, to elucidate taxonomic uncertainties, identify cryptic diversity, investigate the phylogenetic relationship among the species and infer the historical processes that shaped the current Salminus distribution. To assist in taxonomic issues, we employed the traditional DNA barcoding and GMYC COI-based analyses in 110 specimens, representing the four valid species. In both methodologies, eight MOTUs (molecular operational taxonomic units) were identified. Only two species, Salminus affinis and Salminus franciscanus, represented a MOTU each. The species Salminus brasiliensis and Salminus hilarii were represented by two and four MOTU, respectively. These MOTUs are distributed in distinct hydrographic basins where morphological polymorphisms had already been described. The average intraspecific distances greater than the optimal threshold of 1.1% (S. brasiliensis – 3.6%, e S. hilarii – 5%), reinforce the idea of more taxonomic units in Salminus. The multiloci analysis recovered interesting information about the cryptic diversity: the paraphyletic mitochondrial lineages of S. brasiliensis, one from Upper Paraná river and another composed of specimens from the other regions of the Platina basin, formed a unique monophyletic group. For S. hilarii, despite the four MOTUs observed, only three of them were recovered. Therefore, based on multiloci analysis and phylogenetic species concept, we proposed a new taxonomic scenario for Salminus. The genus is now composed of six species: S. affinis, S. franciscanus, S. brasiliensis, S. hilarii, Salminus sp. Amazonas and Salminus sp. Araguaia. The phylogeny reconstruction refuted hypotheses previously proposed. S. affinis, the only trans-Andean species, was the sister species of the other Salminus, which formed two main groups: Northwest group, composed of S. sp. Amazonas and S. sp. Araguaia, and Southeast group, formed by S. brasiliensis, S. franciscanus and S. hilarii. The divergence processes among Salminus began in Later Miocene and it is associated with vicariance and geodispersion events that shaped the hydrological landscape in the past 12 million years. For the first time, it was used a model-based approach in order to test alternative biogeographic scenarios and to distinguish phylogeography signatures among the events responsible for Neotropical fishes’ diversification. We evidenced that the distinct vicariance and geodispersion signatures could be detected in our biological model. A clear description of these species brings in a valuable information for conservation, because, now, six biological units need to be protected. As these species are located in distinct hydrographic basins, each basin becomes one important biogeographic unit to maintain the evolutionary and ecological processes that sustain the species permanence and diversity.